La gestion de l’eau dans les espaces périurbains : entre recomposition et fragmentation territoriales. - Emmanuelle Renaud-Hellier (Cybergeo)
As places of intense socio-spatial mutations and growing tensions on water resources, urban fringes offer heterogeneous institutional responses, often at odds with water districts management challenges. Contemporary evolutions in the Dijon urban area show the relevance of examining jointly processes of urbanization and water supply at functional scales wider than the urban agglomeration alone.